Agroforestry based evaluation of F1 hybrids of Coffea arabica L. - Kumar, Anil; Ganesh, S.; Mishra, M.K.; Rao, N.S.P. (Indian Journal of Agroforestry, 2020)
Most of the commercially grown coffee cultivars are hybrid in nature and exhibit considerable variations in both genotypic and phenotypic characters. These variations are predominantly caused by the genetic makeup of the cultivars as well as environmental conditions. Thus, stabilization of the desirable traits in a genotype before commercial release consumes considerably long period (more than 20years). In order to expedite the breeding programs, exploitation of F1 hybrids assumes great significance in coffee. In the present study, fifteen Coffea arabica F1 hybrids were evaluated for fruit and yield characters. The results revealed that the differences recorded for the reproductive traits in the F1 hybrids derived from three groups of various parental cross were not significant. However, the seasonal variations for these traits among the hybrids were highly significant. The seasonal variation was considerably high for fruit floats and yield characters in the progenies. Highest percentage of heritability and genetic advance was recorded in group of crosses involving tall genotypes (Tall x Tall). The progeny derived from the Dwarf x Tall genotypes exhibited the higher number of fruits/cluster in the F1 generation. The hybrid progenies derived from Cauvery x S.881 (Rume Sudan Wild arabica) and its reciprocal crosses recorded low fruit weight and volume. A similar trend was also recorded in the interspecific hybrids involving C. arabica (C.V Cauvery) x Coffea canephora (cv. CxR) and this could be related to the robusta genome integration.